The kind of friends we used to be - Dowell, Frances O'Roark. (New York : Atheneum Books for Young Readers Scholastic, 2009)
Twelve-year-olds Kate and Marylin, friends since preschool, draw further apart as Marylin becomes involved in student government and cheerleading, while Kate wants to play guitar and write songs, and both develop unlikely friendships with other girls and boys.
Sequel to: The secret language of girls.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Schools -- Fiction